Two distinct alpha 1-adrenoceptor subtypes in rabbit liver: a binding study. - Ohmura, T. (1995)
1. The characteristics of alpha 1-adrenoceptor subtypes present on rabbit liver membranes were determined by radioligand binding and compared with the characteristics of binding in rat liver. 2. In saturation experiments using rabbit liver, [3H]-prazosin bound to two distinct affinity sites (pKD = 10.3 +/- 0.19 and 8.13 +/- 0.17, Bmax = 11.6 +/- 3.3 and 657.8 +/- 198.0 fmol mg-1 protein, respectively). In studies using rat liver, [3H]-prazosin bound to a single affinity site (pKD = 9.98 +/- 0.27, Bmax = 190.5 +/- 38.5 fmol mg-1 protein). 3. In competition experiments, unlabelled prazosin displaced biphasically the binding of 200 pM [3H]-prazosin to the rabbit liver; the resulting two pK1 values (9.85 +/- 0.08 and 8.01 +/- 0.09) were consistent with the affinity constants obtained in the saturation experiments. Two sites were also recognized by doxazosin (pKI 9.73 +/- 0.78 and 8.12 +/- 0.34), 2-(2,6-dimethoxy phenoxyethyl)-aminomethyl-1,4-benzo-dioxane (WB4101) pKI (9.74 +/- 0.32 and 7.57 +/- 0.34) and 5-methylurapidil (pKI 8.69 +/- 0.27 and 6.75 +/- 0.35), and the population of low affinity sites for the three antagonists was approximately 70%. Two distinct affinity constants (pKI 8.55 +/- 0.09 and 7.90 +/- 0.09) were also calculated for alpha-ethyl-3,4,5-trimethoxy-alpha-(3-((2-(2-methoxyphenoxy) ethyl)-amino)-propyl)-benzeneacetonitrile fumarate (HV723). 4. By contrast, [3H]-prazosin binding sites of rat liver membranes were detected as a single population with a high affinity for prazosin (pKI 10.01 +/- 0.08), and doxazosin (pKI 9.67 +/- 0.20) but with a low affinity for WB4101 (pKI 8.25 +/- 0.09), 5-methylurapidil (pKI 7.22 +/- 0.01) and HV723 (pKI 8.88 +/- 0.05). 5. These results indicate the presence of two distinct alpha 1-adrenoceptor subtypes in the rabbit liver, but only a single site in rat liver. The pharmacological characteristics of prazosin-high and -low sites in rabbit liver suggest identity with alpha 1A and putative alpha 1L subtypes, respectively. The site in rat liver is of the alpha 1B subtype.